Multifaceted multinucleated giant cells in oral squamous cell carcinoma. (October 2021) - Pandiar, Deepak; Ramani, Pratibha; Krishnan, Reshma Poothakulath; Monica, K.
Highlights: Multinucleated giant cells are not well studied in oral squamous cells carcinoma. The present paper highlights the role of foreign body type and tumor giant cells in OSCC. Their presence may signify an aggressive clinical course irrespective of the histological grade.